Hubungan Loneliness dengan Stress Akademik pada Siswa Remaja yang Mengalami Broken Home - Mutiara, Qurhoisya; Fahrul, Alfunnafi; Indari, Indari (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Loneliness and academic stress frequently emerge during adolescence, particularly among individuals raised in broken homes, where family disruption may influence emotional stability and adjustment to academic demands. This study aimed to examine the relationship between loneliness and academic stress among adolescents from broken homes. A quantitative correlational design with a cross-sectional approach was employed. The participants were 114 tenth-grade students from two vocational high schools selected through purposive sampling. Data were collected using the UCLA Loneliness Scale Version 3 and the Student-Life Stress Inventory, and analyzed using normality testing and Spearman Rho correlation. The findings revealed a significant positive relationship between loneliness and academic stress, indicating that higher levels of loneliness were associated with higher levels of perceived academic stress. These results highlight the importance of psychosocial support in schools and contribute to the conceptual understanding of social connectedness in adolescent academic stress.